Hemiatrophy of The Cerebral Hemisphere with Contralateral Cerebellar Atrophy: A Case Report (Nepalese Journal of Radiology, 2023)
Childhood cerebral hemiatrophy is a rare clinical condition. Its causes are numerous, but they can be divided into two categories: congenital and acquired. The congenital type develops intrauterine, whereas the acquired type develops early in life, usually before the age of two. Cerebral hemiatrophy syndromes are characterized by a wide range of neurological symptoms. Childhood epilepsy, mental retardation, and neuropsychiatric disorders are common, whereas movement disorders such as highly asymmetric parkinsonism or hemidystonia, as well as neuropsychiatric problems, have been reported in adults. Here we present a 22-year-old patient who presented with refractory seizure. Imaging findings showed hemiatrophy of the right cerebral hemisphere with left cerebellar atrophy.